1997
DOI: 10.1074/jbc.272.22.14093
|View full text |Cite
|
Sign up to set email alerts
|

Direct Demonstration of Geranylgeranylation and Farnesylation of Ki-Ras in Vivo

Abstract: It has recently been reported that Ki-Ras protein can be modified in vitro by farnesylation or geranylgeranylation. However, a previous analysis of Ki-Ras prenylation in vivo found only farnesylated Ki-Ras. In this report it is shown that under normal conditions, Ki-Ras is farnesylated in vivo and when cells are treated with the farnesyl transferase inhibitors B956 or B957, farnesylation is inhibited and Ki-Ras becomes geranylgeranylated in a dose dependent manner. These results have strong implications in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
228
1
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(238 citation statements)
references
References 21 publications
7
228
1
2
Order By: Relevance
“…We have subsequently designed an inhibitor to the closely related enzyme geranylgeranyltransferase I (GGTase I), which transfers a C 20 geranylgeranyl group to the cysteine of CAAX sequences that have a leucine at the carboxyl terminus, and shown that K B -Ras processing and oncogenic signaling was sensitive to this inhibitor (Lerner et al, 1995b). This was consistent with the work of which showed that K B -Ras can be both farnesylated and geranylgeranylated in vitro as well as with the more recent work of Whyte et al (1997) and Rowell et al (1997) in intact human tumor cell lines. The above studies, however, were carried out in cells transfected with an exogenous K B -Ras oncogene and whether or not inhibition of the processing of K-Ras in human tumors requires both FTase and GGTase I inhibitors has not been investigated.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…We have subsequently designed an inhibitor to the closely related enzyme geranylgeranyltransferase I (GGTase I), which transfers a C 20 geranylgeranyl group to the cysteine of CAAX sequences that have a leucine at the carboxyl terminus, and shown that K B -Ras processing and oncogenic signaling was sensitive to this inhibitor (Lerner et al, 1995b). This was consistent with the work of which showed that K B -Ras can be both farnesylated and geranylgeranylated in vitro as well as with the more recent work of Whyte et al (1997) and Rowell et al (1997) in intact human tumor cell lines. The above studies, however, were carried out in cells transfected with an exogenous K B -Ras oncogene and whether or not inhibition of the processing of K-Ras in human tumors requires both FTase and GGTase I inhibitors has not been investigated.…”
Section: Introductionsupporting
confidence: 72%
“…We have therefore made GGTase I inhibitors and used these compounds to give further support for this notion (Lerner et al, 1995b and Figure 1). More recently, K-and N-Ras have been shown to be geranylgeranylated in cells treated with FTase inhibitors (Whyte et al, 1997;Rowell et al, 1997). Although the e ects of FTase inhibitors on normal and malignant cells have been well studied, only recently have the e ects of GGTase I inhibitors been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that while K-Ras and N-Ras can be geranylgeranylated in the absence of farnesylation, H-Ras cannot (Whyte et al, 1997;Rowell et al, 1997). Thus, H-Ras is only activated in the presence of FOL and not in the presence of GGOL, making it a strong candidate for mediating FOL-induced spreading of lovastatin-treated TRAMP cells.…”
Section: Fol's E Ects On Lovastatin-treated Tramp Cells Are Mediated mentioning
confidence: 99%
“…For example, there was no correlation between the Ras mutation status and reversal of transformation as some cancer cells that do not express oncogenic Ras were sensitive to FTI, and inversely, some cancer cells containing activated Ras were resistant to FTI (Cox and Der, 1997;Gibbs and Oliff, 1997;Sebti and Hamilton, 2000;Sebti and Der, 2003). In addition, in vitro and in vivo experiments have shown that K-Ras was geranylgeranylated in cells treated with FTIs (Rowell et al, 1997;Whyte et al, 1997;Sun et al, 1998). Thus, both FTase and GGTase I need to be inhibited to fully block K-Ras isoprenylation (Lerner et al, 1997).…”
Section: Introductionmentioning
confidence: 99%